CREATIVE ECONOMY: ESSENCE AND IMPORTANCE IN ECONOMIC DEVELOPMENT - S.N.Xashimova (Scholar Express Journals, 2025)
The article describes the essence and importance of creative economy. The necessary conditions for the formation of creative economy industries, the main factors and foreign experiences are presented
Keywords: sustainable development; creative economy; creativity; inclusion